Current degradation mechanism of tip contact metal-silicon Schottky nanogenerator - Deng, Shuo (2022)
It has been recently found that a direct current (DC) can be generated through sliding a metal tip (or electrode) against a doped semiconductor if the two materials are of distinct work functions. However, it is also well observed that the DC current generation is degraded if the sliding is repeatedly performed over the same area. Thus, to maintain a stable DC current generation is challenging. In this paper, we present that an ultrathin silicon oxide layer is induced during sliding a platinum coated atomic force microscope tip on a clean doped silicon substrate. With increasing number of sliding over the same area, electron transfer across the tip contacted surface changes from a tribo-voltaic process to a tribo-tunneling process. Moreover, it is also observed that current degradation can be mitigated if the clean silicon substrate is annealed nitrogen. This work not only provides new understanding of electron transfer process in the dynamic Schottky junctions, but also suggests a route for further optimization of the junctions for stable current generation.